MEASUREMENT IN ACCOUNTING. - Homburger, Richard H. (The Accounting Review, 1961)
The comparative studies of accounting and other fields of knowledge have so far been rather rare. It seems odd that in accounting which by its very nature is concerned with monetary, therefore measurable, values, the concept of scientific measurement has been slow in developing. Since ancient times, accounting has been primarily concerned with the recording of the facts of a transaction, such as receipts or disbursements, and the value placed on the transaction was of only incidental significance. Only since the industrial revolution has the measurement of accounting values, as compared to recording techniques, received increased attention. The development and gradual refinement of cost accounting methods involved not only the determination of costs, but also analytical processes and comparisons between cost items which made scientific measurement of the primary data a logical prerequisite. The expansion of the corporate form of business and the resulting necessity of making financial data available to a broader public, on the other hand, led to comparative statements and the establishment of various kinds of ratios which required a refinement of tools in measuring primary balance sheet data.